1985
DOI: 10.1073/pnas.82.5.1503
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Q subregion gene in the murine major histocompatibility complex.

Abstract: We have used restriction enzyme digests, Southern blot analysis, and gene transfer experiments to identify a class I gene in the Q subregion of the murine major histocompatibility complex. By comparisons of class I genes from Q congeneic strains, five restriction fragment length polymorphisms were identified. Further studies of mutant (Qa-2-) and wild-type (Qa-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…It is likely that this structural difference is the direct cause of the change in Qa-2 phenotype from Qa-2+ to Qa-2-in BALB/cBy mice (13). A comparison between class I genes present in the Qa region of B10 and of Qa-2+ BALB/c (2) mouse strains reveals that a gene fusion probably occurred between a pair of ancestral BALB/c genes equivalent to B10 genes Q8 and Q9 (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that this structural difference is the direct cause of the change in Qa-2 phenotype from Qa-2+ to Qa-2-in BALB/cBy mice (13). A comparison between class I genes present in the Qa region of B10 and of Qa-2+ BALB/c (2) mouse strains reveals that a gene fusion probably occurred between a pair of ancestral BALB/c genes equivalent to B10 genes Q8 and Q9 (3).…”
Section: Discussionmentioning
confidence: 99%
“…2b) reveals the absence of a weakly hybridizing 3.5-kb Xba I fragment in BALB/cBy DNA, whereas probe 3 reveals the absence of a 3.7-kb Xba I fragment. A 3.7-kb Xba I fragment, which also hybridizes to a 3' class I gene probe and which is present only in DNA derived from Qa-2+ mouse strains, was described by Flaherty et al (13). Similarly, use ofprobe 1 reveals the loss of a 3.5-kb and a weakly hybridizing 4.8-kb Xba I fragment in BALB/cBy DNA (Fig.…”
Section: Dna Probesmentioning
confidence: 99%
“…Similar to the D region, a spontaneous deletion of class I genes in the Qa region has been noted (34); furthermore, the number of Qa region class I genes differs in the H-2d and H-2b Genetics: Rubocki et al Proc. Natl.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of Balb/cBy, a spontaneously occurring Qa2-Balb/cY subline, indicated that at least part of the structural or regulatory gene controlling the Qa-2 antigen family resides on a 3.7 kb Xbal DNA fragment which is absent in all Qa-2-negative strains tested so far [12]. Mellor et al [ 13] could show that in this subline an unequal crossing-over had occurred between genes 6 and 7 (27.1) of Balb/cBy.…”
Section: The Q Region Of Other Mouse Strainsmentioning
confidence: 99%
“…Mapping studies have uncovered large deletions in the Q region of some haplotypes, involving mostly the H-2K region homolo gous genes Q5 to Q9. It was postulated that in these strains the Q4 gene product might fulfill the Q region function [12]. The exten sive deletion found in the H-2 r strain makes it far more difficult to assign any essential role to the Q region [15].…”
Section: The Evolution Of the Q Regionmentioning
confidence: 99%